Toward a concrete philosophy : Heidegger and the emergence of the Frankfurt School - Immanen, Mikko, 1982- (Signale (Ithaca, N.Y.), 2020)
"In the wake of Martin Heidegger's 1933 Nazi turn, the German Jewish Frankfurt School thinkers Theodor W. Adorno, Max Horkheimer, and Herbert Marcuse understandably saw him as their enemy. This book explores the generative influence that Heidegger's thinking had on the Frankfurt theorists in the Weimar era. As detailed here, Adorno, Horkheimer, and Marcuse saw Heidegger's 1927 magnum opus, Being and Time, as a serious effort to make philosophy relevant for life again and as the most provocative challenge to their nascent materialist diagnoses of discontents of German and European modernity. Drawing on previously unexamined autobiographical testimony, lectures, and discussion notes, as well as Heidegger's 1929 Frankfurt lecture and Black Notebooks, the book reconstructs these overlooked debates, finding in them fruitful intellectual encounters rather than hostile confrontations"--